2016
DOI: 10.1093/abbs/gmw021
|View full text |Cite
|
Sign up to set email alerts
|

Gambogenic acid inhibits LPS-simulated inflammatory response by suppressing NF-κB and MAPK in macrophages

Abstract: Inflammation is a response of body tissues to injury and infection. Compounds that can inhibit inflammation have been shown to have potential therapeutic clinical application. Gambogenic acid (GEA) has potent antitumor and anti-inflammatory activities. Herein, the molecular mechanisms of GEA's anti-inflammatory effect were investigated in lipopolysaccharide (LPS)-stimulated macrophage cells. The results showed that pretreatment with GEA could markedly inhibit interleukin (IL)-1α, IL-1β, tumor necrosis factor-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Previous studies suggested that GNA exhibits stronger and broader anti-tumor effects but lower toxicity than gambogic acid (GA), another component of gamboge which has been clinically applied to treat multiple cancers 13 . It has been reported that GNA can induce apoptosis by inactivation of various signaling pathways in human tumors 14 - 16 . Our previous study has revealed that GNA is cytotoxic toward MM cells under normoxic conditions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that GNA exhibits stronger and broader anti-tumor effects but lower toxicity than gambogic acid (GA), another component of gamboge which has been clinically applied to treat multiple cancers 13 . It has been reported that GNA can induce apoptosis by inactivation of various signaling pathways in human tumors 14 - 16 . Our previous study has revealed that GNA is cytotoxic toward MM cells under normoxic conditions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…BMMs are considered to be osteoclast precursor cells and can differentiate into osteoclast-like multinucleated cells in vitro via the synergistic actions of RANKL and M-CSF [ 11 , 13 ]. NGA is an active component of Garcinia, which is used in traditional Chinese medicine and has been shown to have a beneficial clinical effect on bone fractures and hemostasis and has been reported to have anti-tumor and anti-inflammatory activities [ 10 , 12 ]. However, the effects of treatment with NGA on osteoporosis has not been investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that osteoclast activation and differentiation rely on the receptor activator of NF-κB ligand (RANKL)-related signaling pathway, which plays a crucial role in the differentiation of bone marrow-derived monocyte/macrophages (BMMs) into osteoclasts [ 11 ]. In a preliminary experimental study, we found that NGA suppressed a few key proteins in the NF-κB and mitogen-activated protein kinase (MAPK) pathways, which are closely related to the RANKL/RANK pathway [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are immune cells that play key roles in inflammatory and maintenance of immune homeostasis. In this regard, macrophages are able to eradicate a variety of pathogenic microorganisms by phagocytosis in the body (1), where they are implicated in the regulation of inflammatory occurrence and development by producing pro-inflammatory/anti-inflammatory factors in response to an infection and/or insult stress (2).…”
Section: Introductionmentioning
confidence: 99%